Climate-Smart Agriculture in Kenya - World Bank; International Center for Tropical Agriculture (2016)
The climate-smart agriculture (CSA) concept reflects an ambition to further integrate agricultural development and climate responsiveness. CSA aims to achieve food security and broader development goals under a changing climate and increasing food demand. CSA initiatives sustainably increase productivity, enhance resilience, and minimize greenhouse gas (GHGs) emissions. Increased planning is vital in order to address tradeoffs and synergies between the three pillars: productivity, adaptation, and mitigation. By addressing challenges in environmental, social, and economic dimensions across productive landscapes, CSA practices coordinate the priorities of multiple countries and stakeholders in order to achieve more efficient, effective, and equitable food systems. While the concept is new and still evolving, many of the practices that make up CSA already exist worldwide and are currently used by farmers to cope with various production risks. Mainstreaming CSA requires a critical mapping of successfully completed, on-going practices and future institutional and financial enablers. This country profile provides a snapshot of a developing baseline created to initiate discussion at both the national and global level about entry points for investing in CSA at scale.